Nurses experience of communication with palliative patients in critical care unit: Saudi experience - Alshehri, Hanan; Ismaile, Samantha (International Journal of Advanced Nursing Studies, 2016)
Communication is crucial regardless of a patient's condition in Critical Care Units (CCU). However; communication barriers are common in CCU. In recent years there has been a rapid growth within hospital settings in the provision of palliative care according to patient needs. The purpose of the research study was to investigate nurses’ experiences of communication with palliative patients in CCU. A cross sectional design was conducted using questionnaire. The study sample included nurses who were working in CCU. The total number of completed and submitted questionnaires were 61. The majority of respondents were females. The results show that 49% of respondents have experienced difficulties in palliative care tasks while 41% respondents have complications with communication in palliative care. Also, nurses who took part in this study reported difficultly in discussing decisions such as advanced directives, do not resuscitate orders, and feeding tubes. In conclusion, nurses experience difficulty with communication whilst carrying out palliative care tasks in critical care units. The common causes of communication difficulty are because of the complexity of palliative care tasks, language barriers, shortage of staff and feeling un-empowered. Moreover, there is a lack of education programs centered around enhancing communication difficulties between nurses and palliative patients.